Manfaat Manual Lymph Drainage Vodder Untuk Mengurangi Nyeri Dan Meningkatkan Aktivitas Fungsional Osteoarthritis Lutut - Wibowo, Muh. Nursa'id; , Isnaini Herawati, S.Fis., M.sc (2016)
Background: Osteoarthritis (OA) is a degenerative joint disease, chronic musculoskeletal disorders and is the most common. Inflammation that occurs in osteoarthritis is often associated with cytokine function as mediators of inflammation. Cytokines are glycoproteins, this substance will be transported by the lymphatics. In the development of osteoarthritis has decreased the number of lymph. Manual lymph Drainage Vodder technique will help stimulate the lymph vessels that still exist so that the flow of lymph faster. Objective: This study aimed to determine the ability of manual lymph drainage vodder in reducing and increasing the activity fungssional nyari osteoarthritis of the knee. Methods: This study used a pre-experimental method with the approach of one group pretest-posttest desigan. The number of samples in this study 10 samples. How sampling using purposive sampling method, in accordance with the inclusion and exclusion criteria. Results: Statistical test using the Wilcoxon test results obtained total WOMAC score changes were significant with p = 0.005. The results of WOMAC pain score obtained value of p = 0.005. Results WOMAC stiffness values obtained value of p = 0.003. The results of the WOMAC function disorders acquired value of p = 0.004. Conclusion: With these results we can conclude there are benefits vodder manual lymph drainage to reduce pain and improve functional activity of osteoarthritis of the knee.